FORMULATION AND EVALUATION OF TRANSDERMAL PATCH USING ANTIOXIDANT PHYTOCONSTITUENT - Patel, Deepak Kumar; Gidwani, Bina; Gupta, Anshita; Sahu, Jyoti; Kaur, Dr. Chanchal Deep (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Conventional drug delivery system has many problems so bulk of research has now shifted from synthetic drugs to herbal drugs. This is possible because of the vast variety of bioactive molecules in the plants and their higher safety margin. This present study is focused on the use of curcumin, the active constituent of Curcuma longa (haldi), and belonging to family Zingiberaceae as an antioxidant agent. The main objective of present work was to develop the transdermal patch of curcumin using polymer blends so that minimize the side effects and maximize the therapeutic efficacy. The formulations were also evaluated for weight variation, moisture uptake, thickness, moisture content, and folding endurance. Shows satisfactory results.